Integration of TPACK in Islamic Cultural History Learning: Implications for Teachers’ Pedagogical and Professional Competencies - Nurul Azmi Safitry; Rifqi Muntaqo; Firdaus; Muhamad Yusuf Amin Nugroho; Salza Sabilatul Azira (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This article examines the implementation of TPACK (Technological, Pedagogical, and Content Knowledge) in learning and its implications for the pedagogical and professional competencies of SKI teachers at MTs Negeri 2 Temanggung and MTs Al Mu’min Muhammadiyah Tembarak. This study employs a qualitative multisite field research approach, with data collected through observation, interviews, and documentation. The findings indicate that the implementation of TPACK in SKI learning at both madrasahs has been effectively carried out at the planning, implementation, and evaluation stages. The implications of TPACK for the pedagogical competence of SKI teachers are reflected in their ability to design integrated lesson plans, implement student-centered learning, and utilize information and communication technology (ICT) effectively in both instruction and assessment. Meanwhile, the implications of TPACK for the professional competence of SKI teachers are evident in their deeper mastery of subject matter despite curriculum changes. Teachers demonstrate a clear understanding of learning outcomes and objectives, as reflected in the alignment of teaching modules with the current curriculum. They are also able to contextualize and creatively develop SKI content and are encouraged to continuously enhance their professionalism through participation in training on the use of instructional technology.